Bencana Ekologis dan Tragedi Kemanusiaan di Konawe Utara: Banjir Bandang, Hilangnya Desa, dan Ketidakadilan Lingkungan bagi Orang Culambacu dan Orang Tolaki - Sarlan Adijaya; Danial Danial; Zainal Zainal; Laxmi Laxmi; Raemon Raemon; Erens E. Koodoh; Intang Intang (Fakultas Teknik Universitas Cenderawasih, 2026)
This article analyzes the recurring flash floods in North Konawe Regency which occurred in 2000, 2013, 2016, 2018, 2019, 2020, and 2021 as ecological disasters causally linked to three decades of natural resource exploitation through logging, oil palm plantations, and open-pit nickel mining. Using the dual framework of political ecology and environmental justice, this article argues that these disasters are not neutral natural events, but rather the product of a structured system of injustice: the indigenous Culambacu People and Tolaki People communities who were excluded from decision-making processes regarding extractive permits have borne the greatest burden of the destructive impacts of such exploitation. The most dramatic event was the 2019 flood that devastated Tapuwatu Village, causing losses amounting to Rp 674.8 billion and displacing 9,908 people. The findings demonstrate that the dominant government narrative framing the floods as “natural disasters caused by high rainfall” constitutes a strategic denial that obscures structural responsibility. Empirical data including rates of deforestation, exceeded river carrying capacity, and the chronology of concession expansion correlated with disaster escalation support the ecological disaster thesis. Persistent poverty amid abundant natural resource wealth confirms the condition of a “sacrifice zone,” characterized simultaneously by distributive, recognitional, and procedural injustices.